(untitled) (Homoeopathy for All, 2026)
Varicose veins are among the most common manifestations of chronic venous disease, affecting a significant proportion of adults, particularly women, older individuals, and those with prolonged standing occupations. Conventionally, their development has been explained majorly through venous valve incompetence and mechanical venous hypertension leading to dilation, tortuosity, and venous stasis. However, emerging research suggests that varicose veins are not merely a structural disorder of failed valves, but a complex vascular condition involving endothelial dysfunction, altered shear stress, chronic inflammation, oxidative stress, and extracellular matrix remodelling.